Leading with kindness how good people consistently get superior results - Baker, William F. (New York Brilliance Audio, 2008)
By now, many leaders have realised that when it comes to business, nice guys often finish first. Old fashioned images of corporate callousness and greed have been replaced by a gentler, more human conception of great leadership. But how does one define 'kindness' in the context of business? And what is the best way to 'use' this deceptively simple notion as a guiding principle to lead an organisation successfully into the future? "Leading with Kindness" identifies the attributes successful 'kind' leaders share, showing readers how they can use kindness. Far from presenting a naive idea of kindness consisting of the simple give and take of benefits for supposed loyalty, this realistic book shows leaders how they can use sincerity, honesty, and concern to get the most from their people.
Read by Jim Bond
Keywords: Leadership